BUILD A MANAGEMENT INFORMATION SYSTEM FOR THE JUST IN TIME (JIT) ACHIEVEMENT OF PRINT PRODUCTION PROCESS - Vanya Annisa Syafira; Cholid Mawardi; Mawan Nugraha (Politeknik Negeri Media Kreatif, 2019)
ABSTRACT The Management Information System (MIS) transforms the control system in most of the production processes into automation to achieve the efficiency and effectiveness of production time. If a business is to excel against its competitors, it must be able to meet consumer demand on time, eliminating non-value-added production time and making time spent on activities more efficient. value-added. By researching data by compiling flowcharts and creating tables, authors make direct observations on CV. True printing service. The print production process has machine performance standards which are the standards necessary to determine the capacity of the printing machine. To determine the efficiency of the printing process, it is necessary to know the detailed steps of the process according to the work sequence displayed as a flowchart of the printing process. This flowchart is a key factor in achieving rapid production so that it supports Just In Time (JIT) as the processes in each subsection can be clearly identified. By using a flowchart, any errors that arise in a process can be resolved quickly and correctly so that the results obtained can be optimal and do not interfere with other processes. Therefore, MIS supports the realization of the JIT by facilitating traceability and seeing as early as possible if there is a lack of time and quantity of production. JIT is designed to achieve the most efficient delivery time possible by eliminating all kinds of waste in the production process so that the print production process is optimal. The integration of MIS and JIT is achieved by preparing automatic calculation tables for input, process and output which are the optimal and non-optimal decisions of the printing process.Â